Corporate fraud handbook : prevention and detection - Wells, Joseph T. (Hoboken : Wiley, 2013)
Providing an insider's look into the most prevalent fraud schemes used by employees, owners, managers, and executives, this title provides you with a systematic approach to stop fraud in its tracks before it happens. It brings each scheme to life by using real case studies submitted to the ACFE by the fraud examiners who investigated them.
Preface -- About the ACFE -- Introduction -- Asset misappropriations -- Introduction to asset misappropriations -- Skimming -- Cash larceny -- Appendix: Sample code of business ethics and conduct -- Bibliography -- Index.
Includes bibliographical references (pages 417-424) and index.
oif 24/06/15
Loan
Keywords: Fraud; Corporations -- Corrupt practices; Fraud investigation; Fraud -- Prevention